1989
DOI: 10.1007/bf00254623
|View full text |Cite
|
Sign up to set email alerts
|

Normalised radionuclide measures of left ventricular diastolic function

Abstract: Abnormal left ventricular diastolic function is being increasingly recognised in patients with clinical heart failure and normal systolic function. A simple routine radionuclide measure of diastolic function would therefore be useful. To establish this, the relationship of peak diastolic filling rate (normalized for either end diastolic volume, stroke volume, or peak systolic emptying rate), and heart rate, age, and left ventricular ejection fraction was studied in 64 subjects with normal cardiovascular system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…7 We also confirmed the influence of the filling parameters on the left ventricular systolic function before any treatment. This is in accordance with both angiographic studies and studies of isolated cardiac myocytes, which have shown that diastolic function is necessary to maintain systolic performance.9 10 The absence of variation in age and heart rate, which greatly influence the filling parameters, permitted a good study of the relation between changes in diastolic and systolic function.7 Moreover, we did not study patients with hypertension and coronary artery disease as they are known to have abnormalities of relaxation or to have reduced distensibility.…”
Section: Interrelation Between Systolic and Diastolic Indicessupporting
confidence: 75%
“…7 We also confirmed the influence of the filling parameters on the left ventricular systolic function before any treatment. This is in accordance with both angiographic studies and studies of isolated cardiac myocytes, which have shown that diastolic function is necessary to maintain systolic performance.9 10 The absence of variation in age and heart rate, which greatly influence the filling parameters, permitted a good study of the relation between changes in diastolic and systolic function.7 Moreover, we did not study patients with hypertension and coronary artery disease as they are known to have abnormalities of relaxation or to have reduced distensibility.…”
Section: Interrelation Between Systolic and Diastolic Indicessupporting
confidence: 75%
“…PER and PFR were expressed as fractions of the end-diastolic volume (EDV/s). To minimize the contribution of systole to the PFR, we also expressed the PFR as a fraction of PER [19]. TPFR was also expressed as a ratio of mean cycle length (TPFR/RR).…”
Section: Radionuclide Angiocardiographymentioning
confidence: 99%
“…In a group of 26normal subjects and a group of 30 patients with hypertrophic cardiomyopathy, Stewart and McKenna (1990) found a strong correlation between the first third filling rate and HR (normal, r = 0.71, P < 0.01 ; hypertrophic cardiomyopathy, r=0.66, P<0.01) and between the time for the first third of diastole and HR (normal, r=0.703, P < 0.01 ; hypertrophic cardiomyopathy, r = 0.944, P < 0.01). In a series of 64 subjects with a normal cardiovascular system, Lee et al (1989) observed that PFR, when normalized to EDV or SV, correlated significantly with HR (r = 0.51, P < 0.001 ; r = 0.58, P < 0.001, respectively). In other previous studies (Gerstenbith et al 1983;Bonow et al 1988), no significant correaltion between the LV diastolic parameters and HR was observed.…”
Section: Discussionmentioning
confidence: 94%
“…1983;Bryhn 1984;Seals et al 1986). It has recently been shown that the LV diastolic performance is affected by some physiological and pathological factors, such as age (Fifer et al 1983;Gerstenbith et al 1983;Iskandrian and Hakki 1986;Miller et al 1986;Bonow et al 1988;Lee et al 1989), heart rate (Bahler et al 1983;Bianco et al 1985;Lavine et al 1988;Lee etal. 1989;Adachi etal.…”
Section: Introductionmentioning
confidence: 99%